Small dose of oral gastrografin for computed tomography-based image-guided brachytherapy in patients with uterine cervical cancer. (29th October 2021) - Maemoto, Hitoshi; Ogura, Takuto; Toita, Takafumi; Ariga, Takuro; Hashimoto, Seiji; Kawakami, Yuka; Ishikawa, Kazuki; Takehara, Shota; Heianna, Joichi; Kudaka, Wataru; Aoki, Yoichi; Nishie, Akihiro
Abstract: Oral administration of a water-soluble iodine contrast agent (gastrografin) was reported to assist in the appropriate contouring of the small intestine on computed tomography (CT)-based radiotherapy (RT) planning. The efficacy and optimal dose of gastrografin in CT-based image-guided brachytherapy (IGBT) for cervical cancer remain unknown. This study aimed to investigate the efficacy of pretreatment oral administration of gastrografin at a small dose of 50 ml in CT-based IGBT for cervical cancer. A total of 422 sessions in 137 patients who underwent CT-based IGBT with 50 ml of oral gastrografin (concentration, 3% or 4%) were analyzed. Preparation of gastrografin was judged as effective when the small intestine was contrast-enhanced at the area where the small intestine was in contact with the uterus/adnexa. About 287 out of 422 sessions (68%) were judged as effective with gastrografin preparation. The 135 ineffective sessions were considered as follows: (i) the contrast enhancement of the small intestine was not confirmed (n = 36), (ii) the small intestine was not in contact with the uterus/adnexa despite the confirmation of the contrast enhancement of the small intestine (n = 34), and (iii) gastrografin was absent in the small intestine at the area in contact with the uterus/adnexa, even when gastrografin was observed in the small intestine at the area not in contact with the uterus/adnexa (n = 65). In conclusion, pretreatment oral administration of a small dose gastrografin achieved moderate efficacy for accurate contouring of the small intestine close to the uterus/adnexa in CT-based IGBT for cervical cancer.